Expression of secondary sexual dimorphism in photosynthetic performance of Ilex paraguariensis under contrasted light availability of monoculture and agroforestry during annual rhythmic growth - Rakocevic, Miroslava; Batista, Eunice Reis; de Almeida, Rafael Leonardo; Wendling, Ivar; Ribeiro, Rafael Vasconcelos (Frontiers in Photobiology, 2025)
Plants have developed specific mechanisms to tackle environmental challenges. During one annual period, a dioecious yerba mate with rhythmic growth can present two growth units (GU1 and GU2) intercalated with two rest periods (R1 and R2). We hypothesized that photosynthetic performance will be much higher under monoculture (MO, high light) than under an agroforestry system (AFS, low light) over annual growth and that secondary sexual dimorphism (SSD) will be more expressed during rest than during growth periods. We evaluated the maximum net photosynthesis (Amax), apparent quantum efficiency of CO2 assimilation (Ф), respiration rate in the dark (Rd) and in the light (RL), RL/Rd ratio, maximum apparent rate of electron transport (Jmax), maximum apparent RuBisCO carboxylation rate (Vcmax), Jmax/Vcmax ratio, and chlorophyll indexes in four (two male and two female) clones. Light was reduced by 92%–95% in AFS compared to MO. Photosynthetic traits generally varied over the annual rhythmic growth and revealed higher photosynthetic performance under MO than AFS. Lower Amax and Rd in all clones under AFS than MO occurred together with higher inhibition of respiration by light (low RL/Rd) under AFS than MO. Despite the strong effect of cultivation systems and growth rhythmicity on photosynthetic traits, our data did not suggest that the frequency of SSD in photosynthetic performance (with the exception of the Jmax/Vcmax ratio) was related to the cultivation system or period of rhythmic growth. The SSD was expressed in a higher Chl b index and lower Chl a/b ratio in female than male plants during R2 and GU2, indicating lower sensitivity of females to extreme light conditions of two cultivation systems than males. Higher Amax and similar respiration rates (Rd and RL) in females compared to in males in early vegetative phases after pruning (herein R1 and GU1) could be considered as a fitness strategy of female plants in their additional effort to produce fruits and seeds in latter phases. Our results additionally revealed the importance of the evaluation period when assessing photosynthesis in plant species with rhythmic growth.